What if health care worked like everything else? - Shira Fischer (BMC, 2021)
Abstract Doctors use up-to-date communication technology in their personal lives, but the tools they use to communicate with professional colleagues are much more limited. In light of new research exploring the use of WhatsApp in Israel, this commentary explores the barriers to such use and the technological, legal, and cultural factors that enable adoption of such technologies for medical communication. Common tools can be used for professional collaboration but must be adapted for that use as well as culturally acceptable for broad implementation.